Synthesis of AgI/Bi2MoO6 heterojunctions and their photoactivity enhancement driven by visible light - Jonjana S. (2017)
© 2016 Elsevier B.V. All rights reserved. AgI/Bi 2 MoO 6 heterojunction photocatalysts were successfully synthesized by deposition-precipitation of AgI nanoparticles on Bi 2 MoO 6 nanoplates. The as-synthesized photocatalysts were characterized by XRD, TEM and XPS. Effect of AgI loaded on photoactivity of AgI/Bi 2 MoO 6 heterojunctions was investigated through the photodegradation of rhodamine B (RhB) as a model toxic contaminant under visible light. The 10 wt% AgI/Bi 2 MoO 6 heterojunctions have the highest RhB removal efficiency of 92.89% within 40 min.